Influence of Social Determinants of Health Service Quality on Patient Satisfaction at Undata Hospital, Palu - Sudirman Sudirman; Muhammad Nur Ali; Nurdin Rahman (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: This study aimed to investigate the effect of social determinants of health service quality on patient’s satisfaction at Undata Regional Public Hospital. Methods: The sample consists of 97 inpatients who were treated for at least 2x24 hours. The data analysis technique is Structural Equation Model (SEM) with data analysis tools using SmartPLS software version 3. Results: The results show that the social dimensions of access and quality of education, access to quality health services, and economic stability have no significant effect on service quality. In the dimension of social and community, environmental development influences service quality. Service quality has a significant impact on satisfaction. Access and quality of education, access and quality of health services, social and community context, economic stability have no effect on satisfaction, and the dimension of environmental development influences satisfaction. In the dimensions of access and quality of education, access and quality of health services, economic stability through service quality as an intervening variable has no significant effect on satisfaction. The dimensions of social and community and the dimension of environmental development through the quality of service as an intervening variable have a significant effect on satisfaction at Undata Palu Regional Public Hospital. The level of patient’s satisfaction with health services with a community satisfaction survey value is 3,09 or with good service unit performance. Conclusion: The findings suggest that while some social determinants like education and economic stability do not directly impact service quality or patient satisfaction, factors such as community context and environmental development significantly enhance service quality and satisfaction. These insights underline the importance of a holistic approach to improving healthcare services, focusing on broader social and environmental factors.